Two scales of distribution and biomass of Antarctic krill (Euphausia superba) in the eastern sector of the CCAMLR Division 58.4.2 (55°E to 80°E) - Cox, MJ; Macaulay, G; Madeleine Brasier; Burns, A; Olivia Johnson; King, R; Dale Maschette; Jessica Melvin; Abigail Smith; Christine Weldrick; Wotherspoon, S; So Kawaguchi (2022)
Regular monitoring is an important component of the successful management of pelagic animals of interest to commercial fisheries. Here we provide a biomass estimate for Antarctic krill ( Euphausia superba ) in the eastern sector of the Commission for the Conservation of Antarctic Marine Living Resources (CCAMLR) Division 58.4.2 (55°E to 80°E; area = 775,732 km 2 ) using data collected during an acoustic-trawl survey carried out in February and March 2021. Using acoustic data collected in day-time and trawl data, areal biomass density was estimated as 8.3 gm -2 giving a total areal krill biomass of 6.48 million tonnes, with a 28.9% coefficient of variation (CV). The inaccessibility of the East Antarctic makes fisheries-independent surveys of Antarctic krill expensive and time consuming, so we also assessed the efficacy of extrapolating smaller surveys to a wider area. During the large-scale survey a smaller scale survey (centre coordinates -66.28°S 63.35°E, area = 4,902 km 2 ) was conducted. We examine how representative krill densities from the small-scale (Mawson box) survey were over a latitudinal range by comparing krill densities from the large-scale survey split into latitudinal bands. We found the small scale survey provided a good representation of the statistical distribution of krill densities within its latitudinal band (KS-test, D = 0.048, p -value = 0.98), as well as mean density ( t -test p -value = 0.44), but not outside of the band. We recommend further in situ testing of this approach.